Abrogation of Article 370: The Symbol of National Integrity - Ahmad, Irshad; Parihar, Dr. Seema (Gyan Management Journal, 2023)
A few specific privileges provided to citizens of the Indian state of Jammu and Kashmir were recently abolished by the Indian government. Under Articles 370 and 35A of the Constitution, these rights were provisionally conferred. The Indian government placed some limitations on travel and communication in the Kashmir valley because it anticipates that this step may spark violent protests in the state. Pakistan has spearheaded a defamation campaign against India even though these prohibitions have increasingly been loosened. Over this action, it has even threatened a nuclear exchange. The prime minister of India Mr Narendra Modi said that more than 70,000 lives have been lost over the past thirty years as a result of the particular privileges that the people of Jammu and Kashmir have, which has led to a sense of difference that has been exploited by forces opposed to India’s unity. The neighbourhood was not getting any closer to peace by maintaining the current quo. Hopefully, the elimination of these articles will result in a stronger sense of national integration. Therefore in view of the above statements this dissertation paper is being prepared to study and spread the truth to the all citizens of India that abrogation of article has ended all kinds of privileges and special treatments and has paved the way to the national integration of India